PENGARUH WORK LIFE BALANCE DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP TURNOVER INTENTION MELALUI ORGANIZATIONAL COMMITMENT SEBAGAI VARIABEL INTERVENING PADA PT BERLIAN JASA TERMINAL INDONESIA - OKTAVIANI, HILIN; BUDIONO, (Jurnal Ilmu Manajemen (JIM), 2018)
This research aims to determine and explain the effect of work life balance and perceived organizational support to turnover intention through organizational commitment as an intervening variable at PT Berlian Jasa Terminal Indonesia.This study is using quantitative approach. The population in this research is 292 respondents. The sampling technique that used in this research is proportionate stratified random sampling, and obtained 169 respondents. The analysis technique used in this study is Structural Equation Modeling (SEM) with the help of software AMOS. The results of this research show that work life balance has no significant effect on turnover intention. Work life balance has positive and significant effect on organizational commitment. Perceived organizational support has negative and significant effect on turnover intention. Perceived organizational support has positive and significant effect on organizational commitment. Organizational commitment has no significant effect on turnover intention. organizational commitment can not be an intervening variable between work life balance variable and perceived organizational support variable toward turnover intention.